Implementation of Straight Term, Weighted Average, and Term Weighted Matched-Maturity Fund Transfer Pricing (FTP) on Indonesian Bank - Gregorius Ivan Baskara; Ruslan Prijadi (Green Publisher Indonesia, 2023)
Transfer pricing in the banking industry has a huge impact on maintaining risks and strategic decision-making for preserving competitive advantage in the market. As a best practice, the bank owns an Asset & Liabilities Management (ALM) function assigned to control internal pricing, named Fund Transfer Pricing (FTP), to regulate the inter-division fund pricing between the Funding Division and the Lending Division. While the FTP implementation provisions of a bank are not regulated due to management’s appetite, the FTP calculation methods are definitively established based on several research studies. The most sophisticated method is named Match-Maturity, by reason of matching every banking product’s tenor to the yield curve and calculating them by the repayment behavior. This paper aims to study the significance of the Match-Maturity FTP (MM-FTP) method on a bank in Indonesia which currently apply the Multiple-Pool FTP (MP-FTP) method. To achieve the set objective, the study performed the FTP calculation of identical banking products including samples and all population utilizing MP-FTP and MM-FTP. The result shows 10 out of 11 groups of product and segment experienced over-charged or over-credited employing MP-FTP, which lead to inaccurate evaluation of balance sheet management and performance measurement.